Robotic bilateral axillo-breast versus endoscopic bilateral areola thyroidectomy outcomes of 757 patients - Zhang, Daqi; Wang, Cheng; Sui, Chengqiu; Li, Kunlin; Yang, Mingyu; Xue, Gaofeng; Dionigi, Gianlorenzo; Kim, Hoon Yub; Sun, Hui (Frontiers in Endocrinology, 2023)
Background. Remote endoscopic thyroidectomy (ET) and robotic thyroidectomy (RT) seem to be beneficial in selected situations to avoid anterior neck scars. There are limited data in the literature to determine whether RT via a bilateral axillo-breast approach (RT-BABA) is superior to ET via a bilateral areolar approach (ET-BAA). Therefore, the aim of this study was to evaluate the surgical outcomes of RT-BABA versus ET-BAA. Methods: Between May 2013 and May 2022, 757 patients who underwent RT-BABA or ET-BAA at a high-volume Chinese thyroid center were included. Intraoperative and postoperative outcome parameters were collected and retrospectively analyzed. The moving average method was used to evaluate the learning curve. Results: The proportion of patients older than 45 years was greater in the RT group than in the ET group (14.8% vs. 7.4%, p < 0.001). The percentage of overweight patients was greater in the RT group (28.8% vs. 9.5%, p < 0.001). The number of patients treated for malignant lesions was higher in the RT group (86.8% vs. 75%, p < 0.001). The rate of thyroiditis was higher in the RT group (10.9% vs. 6.6%, p < 0.001). Surgical time was significantly shorter in the RT group (140 vs. 165min, p < 0.001). Drainage volume was higher in the RT group (100 vs. 85ml, p < 0.001). Postoperative hospital stay was shorter in the RT group (3.04 ± 0.44 vs. 3.67 ± 0.89 days, p < 0.001). The cost in the RT group was higher (49627 ± 2795 vs. 25094 ± 3368 yuan, p < 0.001). Transient vocal cord dysfunction was lower in the RT group (2.9% vs. 8.0%, p = 0.003). There was no significant difference between the two groups in the number of central lymph nodes sampled, positive lymph nodes, neural monitoring (EMG) results, and rate of transient hypoparathyroidism. The learning curve for RT was 26 cases, and the operative time for ET was constant throughout the study. Conclusions: RT-BABA is as safe and feasible as ET-BAA. RT-BABA performed better in some surgical outcomes. Further prospective studies are needed to confirm the safety of RT-BABA.